The justice administration system in Peru under the philosophical perspective of human righys - Palma Cueva, Rocío Milagros (2021)
At present, one of the problems that the protection of human rights suffers from a philosophical perspective focuses on the corruption that exists and the poor administration of justice. We must understand that the protection of human rights must not only be limited to the fundamental rights of man, but also to opt for an optimal justice system that can guarantee the safety and protection of citizens. Just as the legal system must guarantee the effectiveness in the application of the norms and in the courts, the problem of corruption must try to diminish so that it is possible to begin to speak not only of a correct administration of justice, but of a correct application from the human rights.